SERAPAN KARBON PADA SISTEM AGROFORESTRY BERBASIS GAHARU (Gyrinops versteegii) DI SRAGEN DAN KARANGANYAR, JAWA TENGAH - Rawana; Hardiwinoto, Suryo; Budiadi; Rahayu, Sri (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2021)
Agroforestry, the practice of growing trees and crops in interacting combinations, has a pivotal role to reduce the CO2 concentration in the atmosphere, and it subsequently sequesters the carbon in part of stems, branches, roots, and crowns of the trees composing their vegetation communities. The objective of the research is to know the carbon sequestration in the three agroforestry practices; those are multilayer tree garden, taungya, and home garden. The research was carried out from April 2017 to March 2018 at Sragen and Karanganyar regency central Java Province. Plot method, with the plot size of 20m x20m for trees, 10m x10 m for pole, and 5m x5m for sapling, was used in the sampling. The carbon sequestration was measured by Chave's allometric equation. The carbon sequestration of above ground the trees planted at taungya was 265.18 kg C ha-1 y-1, in home garden was 236.29 kg C ha-1 y-1, and in multi layer tree garden was 290.14 kg C ha-1 y-1. Seasonal fluctuation of the higest carbon sequestration in home garden occurs on October-December; in multilayer tree garden occurs on January-March; and in taungya occurs on July-September. Key words: Agroforestry practices, G.versteegii, seasonal fluctuation, Carbon sequestration